8 Reducing blood product usage through technology in transplantation. (15th December 2021) - Cross, Nigel; Shaw, Michael; Robertson, Alex; Fenton, Matthew; Issitt, Richard W
Abstract : Background: ABO-incompatible heart transplantation has been used world-wide for over 30 years. This has extended the donor pool and therefore reduced competition for donor organs, especially in young children. However, this technique utilizes a plasma exchange process in which the recipient's circulating volume is replaced with donated packed red blood cells and fresh frozen plasma. Given the shortage of blood products in the UK, we aimed to determine whether we could take existing immunoadsorption technology and create a novel method for transplantation to reduce blood product requirements. Methods: We studied a case series of 10 patients to see if this new method significantly reduced blood product transfusions through the transplant stay and compared to patients that used the plasma exchange process (27 patients). Data were retrospectively extracted from the patient's electronic patient record via SQL query. Data collected included demographics, pre-operative characteristics, intraoperative measurements and postoperative outcomes. Primary outcome measure was volume of blood product transfusions. Results: The total volume of blood products transfused during the hospital admission was significantly lower in the patient cohort treated using immunoadsorption (164 [126–212] ml/kg vs 323 [268–379] ml/kg, p < 0.001). Excluding the volume required for plasma exchange from the analysis, showed significantly lower volumes transfused in the immunoadsorption group (p < 0.001). Furthermore, the age of patients able to be treated using immunoadsorption were significantly older (p < 0.001). Conclusions: The data demonstrate that a significant reduction in blood product usage is possible with the immunoadsorption method compared to the established plasma exchange method. At a time when blood products are in critically low supply, a 50% reduction in blood product requirements allows ABO-incompatible heart transplantation to be facilitated without exerting extra pressure onto an already strained system.